A study of clinical profile and complications in patients with type 2 diabetes mellitus in a tertiary care centre - Mantro, Oshin; Mohanan, Jagadeesan; K., Mahendra Kumar; R., Kannan; A., Gowri Shankar; J., Damodharan; S., Magesh Kumar (International Journal of Advances in Medicine, 2019)
Background: Diabetes is the most common non-communicable disease known today. This study was conducted to assess the clinical profile and complications in patients with type 2 diabetes mellitus. Methods: A prospective study was carried out between April 2017 to April 2018 in patients attending a tertiary care hospital in Chennai. Patients with type 2 diabetes of age 25-80 years, minimum of 5 years duration were enrolled. Results: Out of 66 patients, 23(34.8%) were males whereas 43 (65.2%) were females. Mean age in this study population was 55.36 years with a standard deviation of 11.362. In present study, the mean fasting blood sugar level was 196.12±77.180, mean postprandial blood sugar level was 303.26±115.385 and the mean HbA1C levels was 10.95±2.369. 77.3% were on oral hypoglycaemic agents, 13.6% on insulin and 9.1% on combined therapy with oral hypoglycemic agents and insulin. The complications associated with diabetes found in present study were microvascular complications which include peripheral neuropathy 41(62.1%), retinopathy 31(46.96%), nephropathy 28 (42.42%). Peripheral neuropathy was found to be most commonly associated. Macrovascular complications include cardiovascular disease in 12.12% (n=8) and cerebrovascular disease in 4.54% (n=3). Autonomic neuropathy was found in 69.69% (n=46). Conclusions: The complications of DM are commonly seen in patients with poor glycaemic control. Among microvascular complications, peripheral neuropathy was most commonly seen. Autonomic neuropathy usually goes unnoticed and asymptomatic in most of the individuals. Increasing levels of HbA1c was found to be significantly correlated with neuropathy.